Measuring follow-up care between primary care and specialty behavioral health settings for children and adolescents. Issue 5 (3rd September 2019) - Lynch, Sean; Witt, Whitney; Ali, Mir M.; Teich, Judith; Mutter, Ryan; Gibbons, Brent; Walsh, Christine
ABSTRACT: Although children's behavioral health conditions are regularly presented in primary care, studies of follow-up care that is provided in a specialty behavioral health setting are few. This study measured follow-up care by extracting claims from the Marketscan Medicaid and Commercial databases for outpatient services and prescription drugs for youth aged 2 through 18 years during 2014. Analyses examined whether follow-up care occurred within 28 days. The total percentage of children who received follow-up care was 12.9% (Medicaid) and 13.5% (private insurance). Follow-up care rates are low for the measure. Study findings suggest that additional research is needed in this area.